2021
DOI: 10.5539/ijms.v13n2p20
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Instagram and Influencer Marketing

Abstract: The COVID-19 pandemic and the resulting stay-at-home orders have disrupted all aspects of life globally, most notably our relationship with the internet and social media platforms. People are online more than ever before, working and attending school from home and socializing with friends and family via video conferencing. Marketers and brands have been forced to adapt to a new normal and, as a result, have shifted their brand communication and marketing mix to digital approaches. Hence, this study aims to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…Such behaviour can be controlled by following Lewandowsky and Cook's (2020) suggested 'prebunking' and 'debunking' strategy in cognitively empowering citizens against mass manipulation, although the process appears to be more difficult than previously thought. More aggressive mass media promotion of truth and fact dissemination, along with celebrity, government organization and humanitarian agency-based opinion leadership, are essential in breaking the social networks and chains of disinformation propagation (Francisco et al, 2021). A number of recent studies have advocated such an approach, but our study demonstrates what type of strategic messages need to be crafted in order to counteract deeply rooted ideological sentiments within disinformation campaigns.…”
Section: Theoretical Implicationsmentioning
confidence: 89%
“…Such behaviour can be controlled by following Lewandowsky and Cook's (2020) suggested 'prebunking' and 'debunking' strategy in cognitively empowering citizens against mass manipulation, although the process appears to be more difficult than previously thought. More aggressive mass media promotion of truth and fact dissemination, along with celebrity, government organization and humanitarian agency-based opinion leadership, are essential in breaking the social networks and chains of disinformation propagation (Francisco et al, 2021). A number of recent studies have advocated such an approach, but our study demonstrates what type of strategic messages need to be crafted in order to counteract deeply rooted ideological sentiments within disinformation campaigns.…”
Section: Theoretical Implicationsmentioning
confidence: 89%
“…By conducting an online survey, it was found that younger Instagram users, aged 18-24, tend to follow influencers, especially those who they identify with, and those who are transparent and authentic in advertising. They tend to trust such influencers and are more willing to purchase goods recommended by them (Francisco et al, 2021). In Indonesia, the government´s decision to stay at home and work from home was considered/perceived as detrimental, as not everybody could work from home, and many employees were laid off.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a modern way, producers should engage the influencer and other customers who satisfy the honey product of brand X. Fransisco et al (2021) suggested that more brands used influencers to market their products during this pandemic. Many brands have had to also change their way of promotion by advocating the use of masks and social distancing.…”
Section: Honey Productmentioning
confidence: 99%